Peran Satuan Polisi Pamong Praja Kabupaten Karawang Dalam Penertiban Gelandangan Dan Pengemis - Nur Agustin, Nabila; Purnamasari, Hanny; Ramdani, Rachmat (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of the Civil Service Police Unit (Satpol PP) of Karawang Regency in the control and regulation of homeless people and beggars (gepeng). The increasing presence of gepeng in the Karawang area has led to various social issues, ranging from disturbances to public order to the deterioration of urban aesthetics. This research employs a qualitative approach using a case study method. The theoretical framework is based on Keith Davis's role theory, which includes six indicators: role expectation, role perception, role performance, role conflict, role ambiguity, and role overload. Data were collected through observation, structured interviews, and documentation involving informants from Satpol PP, homeless individuals and beggars, as well as local community members. The findings reveal that the role of Satpol PP in regulating gepeng remains suboptimal. Several inhibiting factors include limited human resources, lack of synergy among regional apparatus organizations, and low public awareness, as many residents continue to give money or goods to gepeng. Although Satpol PP has established clar standard operating procedures, their implementation tends to be reactive and fails to create a deterrent effect. Therefore, a more comprehensive and sustainable approach is needed, involving the community and other relevant agencies in addressing the issue of gepeng in Karawang Regency. Keywords: Role, Civil Service Police Unit, Control, Homeless, Beggars, Karawang